Nanotecnología aplicada a los fluidos de cementación: antecedentes y nuevas tendencias de fluidos en pozos verticales (2022)
In recent years, the oil industry has sought solutions to minimize problems related to cementing fluids, such as deficiencies in the physicochemical properties of cement (chemical stability and oxidation), poor flocculation, presence of fractures, among others. One of the most promising solutions to mitigate the problems related to cementing fluids is the use of nanomaterials. Investigations based on the application of nanomaterials to improve cementing fluids include various types of nanofluids, prepared at different concentrations, working conditions and particle sizes, for which it is necessary to determine which type of nanomaterial is the most suitable to improve cementing fluids. different properties of these fluids.